Study on predatory mites of Aceria tristriatus (Nalepa, 1890) from Hamedan and Lorestan provinces, Western Iran - Mohammad Ahmad-Hoseini; Mohammad Khanjani; Roya Karamian (Persian Journal of Acarology)
The walnut leaf gall mite (Aceria tristriatus) is one of the major pests of walnut in western Iran. Therefore, a study to determine the predatory mites associated with this pest in Hamedan and Lorestan provinces was carried out during 2014–2017. In this survey, totally 10 species belong to six genera and three different families including Phytoseiidae: Kuzinellus kuzini Wainstein, Typhlodromus bagdasarjani Wainstein & Arutunjan, Typhlodromus khosrovensis Arutunjan, Euseius finlandicus Oudemans; Iolinidae: Neopronematus iranensis Ahmad-Hosseini et al., Neopronematus solani Ripka et al., Pronematus rykei Meyer & Rodrigues; Tydeidae: Tydeus caryae Khanjani & Ueckermann, Tydeus goetzi Schruft, and Tydeus electus Kuznetzov were collected and identified. Kuzinellus kuzini Wainstein had the highest frequency and distribution in this survey. Among the collected species, Typhlodromus khosrovensis, Typhlodromus bagdasarjani, E. finlandicus, N. solani, Tydeus caryae, Tydeus goetzi and Tydeus electus are re-described in the present paper. Tydeus goetzi and Neopronematus solani are reported for the first time for Hamedan and Lorestan provinces.